ECONOMIC TRANSFORMATION OF INDONESIA IN THE ERA OF DIGITAL 5.0: CHALLENGES AND OPPORTUNITIES - Adih Supriadi; Loso Judijanto; Ahmad Rizani; Al- Amin; Zulkifli (INTERNATIONAL JOURNAL OF FINANCIAL ECONOMICS, 2024)
Indonesia, a nation at the crossroads of economic transformation, is confronted with a unique set of challenges and opportunities in the era of Digital 5.0. This paper explores the implications of Digital 5.0 on Indonesia's economic landscape, emphasizing the key challenges and opportunities. The challenges encompass the digital divide, regulatory complexities, cybersecurity risks, and the imperative of a skilled workforce. These challenges necessitate a collaborative and forward- thinking approach involving government, private sector, and civil society. On the flip side, Indonesia's digital economy offers opportunities in e-commerce, fintech, startups, smart manufacturing, and e-governance, paving the way for innovation, job creation, and inclusive growth. The path forward involves bridging the digital divide, crafting a conducive regulatory environment, investing in cybersecurity and education, and promoting entrepreneurship. Indonesia's success in this transformative era hinges on its ability to navigate the evolving digital landscape and position itself as a global economic force.